Review of the genus Micraspis Chevrolat, 1836 (Coleoptera: Coccinellidae) from China and Laos, with description of three new species - Zhu, Zi-Hao; Chen, Xiao-Sheng; Peng, Zheng-Qiang; Toulakhom, Chantharath; Wang, Xing-Min (Zootaxa, 2026)
The genus Micraspis Chevrolat, 1836 from China and Laos is reviewed. Fourteen species are described and illustrated, including three new species, M. elongata Zhu, Chen & Wang sp. nov., M. filapicis Zhu, Chen & Wang sp. nov., and M. varimacula Zhu, Chen & Wang sp. nov. M. pusilla Poorani, 2014, M. tenuilinea (Walker, 1859) and M. kiotoensis (Nakane & Araki, 1960) stat. rev. are firstly recorded from China. The genus Micraspis is firstly recorded from Laos. A key and a distribution map of the known species are also presented.